Elie Wiesel : confronting the silence - Berger, Joseph 1945- (Jewish lives, 2023)
As an orphaned survivor and witness to the horrors of Auschwitz, Elie Wiesel (1928-2016) compelled the world to confront the Holocaust with his searing memoir Night. How did this soft-spoken man from a small Carpathian town become such an influential figure on the world stage? Drawing on Wiesel's prodigious literary output and interviews with his family, friends, scholars, and critics, Joseph Berger seeks to answer this question